Energy drinks consumption-prevalence, associations, awareness on health risks and its potential relationship with subsequent substance use among residential students in university of colombo - De Silva, D.K.M.:Dissanayake, D.M.B.M.: Thilakarathna, P.K.I.S.: Kumara, G.L.S.: Shamen, U.J.L.: Dharmasiri, W.D.D.S.: Rozni, A.G.M.: Minna, N.L.F.: Ubhayawardana, D.L.N.L.: Elvitigala, D.A.S. (University of Colombo, 2023)
Introduction: The global Energy Drink (ED) market is continuously expanding, and it’s more often oriented towards youth and young adults. This has raised concerns among healthcare professionals that young adults who consume ED may harm their health. Currently, there is a trend for subsequent substance use with this ED consumption, but not well studied. Objective: To assess the prevalence of ED consumption, associations, awareness of health-related risks, and its potential association with the use of substances among residential undergraduates at University of Colombo. Methods: This study was a descriptive cross-sectional and 361 undergraduates who resided in all hostels of the university were enrolled. An online self-developed, pre-validated questionnaire was distributed to gather information on socio-demographic data, frequency of consumption, reasons, associations behind the consumption, awareness of the negative effects, co-relation between ED consumption and subsequent substance use. Data were analyzed to obtain percentage, frequencies and relationship. Results: Majority of the participants were males while 52.9% were aged between 23 -25 years. The prevalence of ED consumption was 31% and most were infrequent consumers (47.3%). Primary reason for consumption was to enjoy the taste. 89.8% of the participants had poor awareness regarding health-related effects. Level of awareness, age, gender, monthly income of the family, academic year, part-time jobs, and sexual activity status (p<0.05) were positively associated with ED consumption. ED consumption was statically significant (p<0.05) with Alcohol, Cigarettes, Cannabis, Marijuana, and Tobacco use. Conclusions: This study showed a high incidence of ED intake among undergraduate hostellers of the university and identified several associated factors for consumption such as taste, social influence and doing sports. The majority of the hostellers had poor awareness regarding health-related risks linked with ED consumption. Findings of this study demonstrate that consuming ED is potential risk factor for substance-abuse.
Keywords: Energy Drinks; Undergraduate hostellers; Association; Substance use